TRANSFORMASI LIVING HADIS DALAM PLATFORM DIGITAL: STUDI KASUS UNGKAPAN MASYÂ ALLÂH TABÂRAKALLAH DI KALANGAN SELEGBRAM BANJARMASIN - Hanafi, Hanafi (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
This study aims to explore the transformation of living hadith in the context of digital platforms, with a particular focus on the use of the phrase "Masyâ Allâh Tabârakallah" by influencers (Selebgram) in Banjarmasin. Living hadith refers to the application of the teachings and values of the hadith of Prophet Muhammad SAW in everyday life. In the digital age, social media (especially instagram) has become a significant medium for the dissemination and adaptation of religious values. The methodology used in this study is qualitative, involving content analysis of posts on Instagram, as well as in-depth interviews with selected influencers in Banjarmasin. This research identifies the motives, contexts, and impacts of using the phrase "Masyâ Allâh Tabârakallah" in influencers' posts and how this reflects the transformation of hadith values in the digital environment. The findings indicate that the use of "Masyâ Allâh Tabârakallah" by influencers serves not only as a religious expression with spiritual significance and self-protection from the unseen but also as a strategy to build image and relationships with followers. This phrase functions as a form of acknowledgment of beauty or success considered a blessing from Allah and as protection from envy or "ain" (evil eye). The study suggests that living hadith undergoes significant adaptation in the social media environment, where influencers play a crucial role in disseminating and internalizing religious values to a broader audience. This research contributes to understanding how religious values can transform and interact with digital culture, offering insights for further research on the role of social media in the development of Sunnah values in the digital age.